Romance on the high seas [videorecording (DVD)] - Epstein, Julius J., 1909-2000; Epstein, Philip G.; Day, Doris, 1922-2019; Carson, Jack, 1910-1963; Paige, Janis (Warner Bros. Home Entertainment, 2017)
Romantic misunderstandings abound when spouses suspect each other of being unfaithful, and a nightclub singer takes a cruise under a false identity.